Étienne Gilson and Henri Gouhier’s “Malebranche Moment” - Richard Fąfara (Studia Gilsoniana, 2025)
Professor Delbos’ critique of Gilson’s undergraduate essay as not explaining Malebranche’s intense criticism of Aristotle and the scholastics helped turn Gilson into a sensitive scholar. In 1921, the “Malebranche Moment” began when Gilson agreed to direct Gouhier’s doctoral thesis and suggested “Malebranche: the last of the great Augustinian Scholastics” as a fruitful research topic. Gouhier presented Malebranche as a Christian philosopher influenced by Augustine and Bonaventure; Malebranche’s virulent anti-Aristotelianism and anti-scholasticism originated from the apologetic nature of Malebranche’s thought. The profound movement of renovation, understanding, and presentation that Malebranche’s philosophy attained in the early 20th century took its definitive form in Gouhier’s work. Under Gilson’s guidance, Gouhier gave decisive authority to Malebranche being taken seriously in academia, an honor previously not accorded to him. Gilson and Gouhier’s interpretations of Malebranche differed because of their divergent methods and different understandings of the history of philosophy, Christian philosophy, and, ultimately, philosophy itself.